2016
DOI: 10.3892/or.2016.5186
|View full text |Cite
|
Sign up to set email alerts
|

Pien Tze Huang suppresses VEGF-C-mediated lymphangiogenesis in colorectal cancer

Abstract: Abstract. Colorectal cancer (CRC) is one of the most common malignancies worldwide. The majority of patients are not suitable for surgery due to the presence of metastatic disease at the time of diagnosis, which has led to a high mortality rate for patients with CRC. Lymphangiogenesis, formation of new lymphatic vessels, plays an critical role in cancer progression particularly in cancer metastasis. Vascular endothelial growth factor-C (VEGF-C) has been previously demonstrated to play a pivotal role in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Pien Tze Huang (PZH), a well-known TCM formula that originated in the Chinese Ming Dynasty >450 years ago, has been widely used in China and Southeast Asia as a remedy for various diseases, including cancer (36). It was previously demonstrated that PZH may inhibit colon cancer growth via multiple mechanisms (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) and PZH has exhibited promising therapeutic effects in clinical trials regarding HCC (50,51). However, the effect of PZH on HCC, including on miR-16 expression level, has not been evaluated; therefore, the present study aimed to explore the effect of PZH on the proliferation and apoptosis of the HCC BEL-7402 cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Pien Tze Huang (PZH), a well-known TCM formula that originated in the Chinese Ming Dynasty >450 years ago, has been widely used in China and Southeast Asia as a remedy for various diseases, including cancer (36). It was previously demonstrated that PZH may inhibit colon cancer growth via multiple mechanisms (37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) and PZH has exhibited promising therapeutic effects in clinical trials regarding HCC (50,51). However, the effect of PZH on HCC, including on miR-16 expression level, has not been evaluated; therefore, the present study aimed to explore the effect of PZH on the proliferation and apoptosis of the HCC BEL-7402 cell line.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products, including TCM, have received great interest since they have long been used to clinically treat inflammatory diseases and are relatively toxicity-free (9)(10)(11)(12). PZH is a well-known TCM formula which has been used in China and Southeast Asia for centuries to clinically treat a variety of inflammatory diseases (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). However, the precise mechanism of anti-inflammatory activity of PZH remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Using different human colorectal cancer cell lines and human LECs model stimulated by VEGF-C, Lin et al evaluated the effects of PZH on tumor metastasis and VEGF-C expression. It was found that PZH suppresses lymphangiogenesis via the downregulation of VEGF-C, which may be a potential molecular mechanism of inhibition of metastasis of colorectal cancer by PZH (Lin et al, 2016).…”
Section: Tcm Formula (Table 6) Experimental Research Of Tcm Formulamentioning
confidence: 99%